Pushed to the Margins and Stretched to the Limit: Experiences of Freelance Eldercare Workers During the Covid-19 Pandemic in the Netherlands. Issue 1 (3rd April 2021) - Duijs, Saskia Elise; Haremaker, Anouk; Bourik, Zohra; Abma, Tineke A.; Verdonk, Petra
Abstract : Eldercare professionals engaged in precarious work in the Netherlands faced shortages in personal protective equipment (PPE), testing, and staffing during the COVID-19 pandemic. This qualitative study of the health, financial situations, and paid and unpaid caring responsibilities of freelance eldercare workers illustrates how labor market inequalities have been (re)produced and exacerbated during the pandemic. Freelancers were pushed toward the margins of the labor market, working risky shifts and compromising their own interests, while unprotected by organizations, social security, or political efforts. Consequently, these workers were stretched to limits where they could no longer attend to their own health or to their paid and unpaid care responsibilities. The study places these empirical findings within Nancy Fraser and Rahel Jaeggi's theoretical work on capitalism, illustrating how eldercare workers found themselves at the center of boundary struggles during the pandemic. HIGHLIGHTS In the Netherlands, paid eldercare workers increasingly opt for freelance care work. During the pandemic freelance eldercare workers were seen as a health risk for clients. Some lost assignments; others were asked to work with insufficient PPE. As a result, many struggled with moral and financial dilemmas. Unions and other players in the Netherlands hold conflicting views on freelancers in eldercare. These views stand in the way of building an alliance to enhance the situations of all working in the sector.